Pharmacogenomics of warfarin in populations of African descent - Suarez-Kurtz, Guilherme (Blackwell Science Inc, 2013)
Warfarin is the most commonly prescribed oral anticoagulant worldwide despite its narrow therapeutic index and the notorious inter- and intra-individual variability in dose required for the target clinical effect. Pharmacogenetic polymorphisms are major determinants of warfarin pharmacokinetic and dynamics and included in several warfarin dosing algorithms. This review focuses on warfarin pharmacogenomics in sub-Saharan peoples, African Americans and admixed Brazilians. These ‘Black’ populations differ in several aspects, notably their extent of recent admixture with Europeans, a factor which impacts on the frequency distribution of pharmacogenomic polymorphisms relevant to warfarin dose requirement for the target clinical effect. Whereas a small number of polymorphisms in VKORC1 (3673G > A, rs9923231), CYP2C9 (alleles *2 and *3, rs1799853 and rs1057910, respectively) and arguably CYP4F2 (rs2108622), may capture most of the pharmacogenomic influence on warfarin dose variance in White populations, additional polymorphisms in these, and in other, genes (e.g. CALU rs339097) increase the predictive power of pharmacogenetic warfarin dosing algorithms in the Black populations examined. A personalized strategy for initiation of warfarin therapy, allowing for improved safety and cost-effectiveness for populations of African descent must take into account their pharmacogenomic diversity, as well as socio-economical, cultural and medical factors. Accounting for this heterogeneity in algorithms that are ‘friendly’ enough to be adopted by warfarin prescribers worldwide requires gathering information from trials at different population levels, but demands also a critical appraisal of racial/ethnic labels that are commonly used in the clinical pharmacology literature but do not accurately reflect genetic ancestry and population diversity.